2012
DOI: 10.4236/ajac.2012.32021
|View full text |Cite
|
Sign up to set email alerts
|

RP-HPLC Method for the Simultaneous Determination of Lisinopril and NSAIDs in API, Pharmaceutical Formulations and Human Serum

Abstract: High performance liquid chromatographic method was developed valdated and applied for the simultaneous determi- nation of lisinopril and NSAIDs in bulk, pharmaceuticals formulations and human serum. A Purospher star C18 (5 µm, 25 × 0.46 cm) column was used with mobile phase consisting of methanol: water: acetonitrile (80:17.5:2.5 v/v, pH 3.0) and quantitative evaluation was performed at 225 nm with a flow rate of 1.0 mL?min–1. The retention time of lisinopril was 2.2 min while naproxen, flurbiprofen, diclofena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Our research group has worked on HPLC methods for the quantitation of inhibitors as captopril, enalapril and lisinopril alone and in combination with fosinopril and diclofenac sodium [12][13][14][15][16] in bulk drug, pharmaceutical formulations and serum. Sultana et al [15] have also reported simultaneous methods for the determination of various ACE inhibitors with co-administered drugs as lisinopril with H 2 antagonists [17], NSAIDs [18] and with statins [19].…”
Section: Reported Methods Of Analysismentioning
confidence: 99%
“…Our research group has worked on HPLC methods for the quantitation of inhibitors as captopril, enalapril and lisinopril alone and in combination with fosinopril and diclofenac sodium [12][13][14][15][16] in bulk drug, pharmaceutical formulations and serum. Sultana et al [15] have also reported simultaneous methods for the determination of various ACE inhibitors with co-administered drugs as lisinopril with H 2 antagonists [17], NSAIDs [18] and with statins [19].…”
Section: Reported Methods Of Analysismentioning
confidence: 99%
“…[11][12][13][14] The HPLC system was composed of a pump (LC-10AS; Shimadzu Co., Kyoto, Japan), an auto-injector (SIL-10A, Shimadzu Co.), a UV detector (SPD-10A, Shimadzu Co.), an analysis system (Smart Chrom, KYA TECH Co., Tokyo, Japan), and a column. A C8 column (COSMOSIL 5C8-MS, 5 µm, 4.6×150 mm; Nacalai Tesque, Kyoto, Japan) was used for mexletine and a C18 column (TSKgel ODS-100V, 3 µm, 4.6×150 mm, Tosoh Co., Tokyo, Japan) was used for the other drugs.…”
Section: Determination Of Content Uniformitymentioning
confidence: 99%
“…Our research group has developed and validated simultaneous methods for the co-adminstered drugs as rosuvastatin with NSAIDs [11] and with alprazolam and diclofenac [12]. Lisinopril, captopril [13,14] and metformin [15] have also been simultaneously determined with NSAIDs.…”
Section: Enalapril Maleate Is Chemically Described As (S)-1-[n-[1-(etmentioning
confidence: 99%